2012
DOI: 10.1174/217119712799240224
|View full text |Cite
|
Sign up to set email alerts
|

Place identity and residential satisfaction: Differences between native and immigrant populations

Abstract: This research focuses on the concepts of place identity, social identity, residential satisfaction and community participation among immigrant and native populations. Two sample populations were analyzed: 148 Latin Americans and 150 native Spanish residents of Málaga. Comparisons drawn between the groups yielded higher levels of place identity -with the neighbourhood, city and country-, residential satisfaction and community participation among the native population. Immigrants displayed greater place identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 25 publications
0
8
0
3
Order By: Relevance
“…These results might well indicate, in accordance with previous studies (Sam et al, 2012), the lesser importance of spatial aspects when it comes to measuring questions relative to quality of life in residential environments, but they could also point to the need to explore in greater depth which these aspects are and how they affect the bonds established by inhabitants with the contexts they inhabit. This is a key element in processes of urban planning, since residential satisfaction is a highly relevant aspect to improve quality of life in general (Amérigo & Aragonés, 1997); also, greater residential satisfaction is key to greater place identity and higher levels of social participation, encouraging residents to integrate in local social and community life (Ríos & Moreno-Jiménez, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…These results might well indicate, in accordance with previous studies (Sam et al, 2012), the lesser importance of spatial aspects when it comes to measuring questions relative to quality of life in residential environments, but they could also point to the need to explore in greater depth which these aspects are and how they affect the bonds established by inhabitants with the contexts they inhabit. This is a key element in processes of urban planning, since residential satisfaction is a highly relevant aspect to improve quality of life in general (Amérigo & Aragonés, 1997); also, greater residential satisfaction is key to greater place identity and higher levels of social participation, encouraging residents to integrate in local social and community life (Ríos & Moreno-Jiménez, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Anton and Lawrence (2014) find that in areas in Australia that are at risk of bush fires, rural residents have a stronger regional identity than do those of urbanised areas. Ríos and Moreno‐Jiménez (2012) compare natives and immigrants in Málaga, Spain, and find a higher place identity among natives at several levels (neighbourhood, city and country). Immigrants identify more with a place if they live there longer or are employed there and own their home.…”
Section: Regions and Identitymentioning
confidence: 99%
“…Howley et al (2009) believe that it is not only high density per se that is the source of dissatisfaction for residents but rather other related factors such as environmental quality, noise, lack of community involvement, traffic and lack of services and facilities. Ríos & Moreno-Jiménez (2012) focused on the concepts of place identity, social identity, residential satisfaction and community participation among immigrant and native populations. They found that greater place identity was seen to be linked with greater community participation and residential satisfaction.…”
Section: Migration As Anmentioning
confidence: 99%